Serum vitamin D level was not associated with severity of ventilator associated pneumonia - Yaghoobi Mojtaba Hedayat; Taher Abbas; Seifrabie Mohamad Ali; Sabahi Mohammadmahdi; Rahimi-Bashar Farshid (Sciendo, 2019)
Background and Objective. Vitamin D deficiency is considered one of the most common nutritional deficiencies associated with weakened immune system and increased likelihood of sepsis. The current study was conducted to investigate the association between serum vitamin D level and the severity and prognosis of ventilator associated pneumonia (VAP) in inpatients in intensive care unit (ICU).